SOME ASPECTS OF INTERNATIONAL LEGAL REGULATION OF ECONOMIC COOPERATION IN THE SCO - SHERIAZDANOVA, Kamilla; KONDYKEROVA, Karlygash (CENTRAL ASIA AND THE CAUCASUS, 2013)
The SCO has become an influential international structure today. Throughout its existence, the Organization has acted as an important mechanism for ensuring regional stability, as well as sustainable political and economic cooperation in the area in which it operates. Today, the SCO is playing an increasingly efficient part in building the global security system, which is largely due to the new threats and challenges the world community now faces. Kazakhstan’s chairmanship in the SCO ended with a celebratory sitting of the Council of Heads of Member States held on 15 June 2011 in Astana. At this meeting, the Astana declaration of the SCO’s Tenth Anniversary was adopted, which states that during this time, the Organization has successfully advanced from its institutionalization to the establishment of efficiently functioning mechanisms of interaction in different spheres. The SCO is a regional international organization, the main tasks of which are strengthening stability and security in the broad area that joins the states belonging to it, fighting terrorism, separatism, extremism, and drug trafficking, developing economic cooperation and energy partnership, and enhancing scientific and cultural interaction. The SCO is an essentially new model of geopolitical integration that makes it possible to unite the interests of Central Asia, Russia, and China. This statement is based on the experience of the SCO member states that are pooling their efforts to oppose non-traditional threats to security in Central Asia—terrorism, flagrant fundamentalism, drug crimes, and separatism. Of course, there are political reasons for unifying the countries within the SCO borne by the desire to ensure security in the region, while economic factors predominate in the traditional integration models. In this case, free trade is the springboard for forming a political union. However, despite the prime importance of the political component in the SCO’s activity, it is the economic factors that make it possible to oppose the negative trends in the life of the Central Asian region.